The Building of Relevant Morality for Politics and Law. The Contributions of Deontological Ethics and Kantian Rooted Communicative Ethics - Bustamante Alarcón, Reynaldo (2009)
This work aims to study the contributions of deontological and communicative ethics of Kantian roots throughout history, focusing on the importance of these for the construction of a moral that serves as a basis for the study and practice of politics and law taking into account tells the principle of human dignity. The first part explains some categories and elementary details about morality that will serve to adequately understand the rest of the text, among which are personal morality, social morality, types of ethics, among others. After that, the principles of autonomy and universality are developed, which based on the principle of human dignity manage to create a certain balance that gives rise to a deontological ethic based on the thought of Immanuel Kant. In the third part, the discursive principles of universalization and adaptation are developed, which give rise to a communicative ethic that also has a large part of its base in the ideas of Kant. Finally, a brief reflection is offered regarding the study of deontological and communicative ethics, which can contribute to the construction of a free, open, plural and democratic society, in order to materialize the principle of human dignity.